An integrated automatic aviation meteorological instrument system at C. S. I. airport, Mumbai (MAUSAM, 2012)
An ‘Integrated Automatic Aviation Meteorological Instrument System’ (IAAMS) is installed atMumbai International Airport in May-2008. The system is State-of-the-Art and has features like automatic generation ofaviation reports; METAR / SPECI, AFTN (Aeronautical Fixed Telecommunication Network) connectivity fordissemination of aviation weather reports to user agencies and ATIS (Automatic Terminal Interface System) forautomatic broadcasting of aviation weather reports to airborne pilot. Besides these features system is having facility toenter manually weather parameter for which sensors are not available such as cloud coverage, past weather, presentweather for generation of aviation reports. The system meets the requirements of operational desirable accuracy ofInternational Civil Aviation Organization (ICAO, 2004) and vector averaging of winds as per World MeteorologicalOrganization guidelines (WMO, 1992). The paper is mainly focusing on the different technical features of this newsystem along with its observational response in last one year at Mumbai airport. Similar system has been installed at othermajor airports; New Delhi (4 sites), Chennai, Hyderabad, Bangalore, Amritsar, Jaipur, and Guwahati. The system issupplied and installed by Telvent Company, Australia.